DEVELOPMENT OF TRANSVERSAL SKILLS IN PRIMARY SCHOOL (CLASSES 1-3): CONTEXT OF LIFELONG LEARNING - Pelnēna, Ivita; Medveckis, Arturs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The primary task of the 21st century education is not anymore to transfer continuous information, but the skill to acquire independently and learn this knowledge during lifetime. In the future, the development of transversal skills plays an important role in the educational process. Transversal skills, such as critical thinking and problem-solving, creativity and innovation, self-guided learning, cooperation, civic participation and digital literacy, are raised in the framework of Education Reform in Latvia (Skola 2030, 2017). The beginning of the learning process during the stage of primary school is an essential step in transversal skills acquisition, particularly emphasizing the impact of the Classes 1-3 stage, on the further learning process. According to the outcomes determined in the standard of primary education to be achieved, it is necessary to develop significantly transversal skills in this stage, as well as observe carefully the changes in children’s age development that affect the possibilities of transversal skills development.The goal of the research:  analyse the development of transversal skills in primary school (Classes 1-3).Research method: content analysis of the education content regulating documents and scientific literature.